Lessons in Theory of Change from a Series of Regional Planning Workshops - Schuetz, Tonya; Förch, Wiebke; Thornton, Philip K.; Wollenberg, Eva Karoline; Hansen, James; Jarvis, Andy; Coffey, Kevin; Bonilla Findji, Osana; Aggarwal, Pramod K.; Sebastian, Leocadio S.; Zougmoré, Robert B.; Kinyangi, James; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is using theory of change (TOC) planning to specify research outputs, partnerships needed to produce outputs, and a plausible hypothesis on how these outputs will contribute to development outcomes. This learning note is part of a series to capture the process, progress and lessons from CCAFS in its endeavor to plan, implement and deliver research for development with a strong focus on outcome delivery. The portfolio for 2015 includes about 80 newly contracted projects in five CCAFS target regions (South and Southeast Asia, East and West Africa and Latin America) with a value of between $5-15 million in each region.